Cloacal gland growth differences in high and low plasma corticosterone stress response line male quail reared under short daylengths - Satterlee, Daniel G. (2007)
Mail quail selected (generation 32) for reduced [low stress (LS)] or exaggerated [high stress (HS)] plasma corticosterone stress response to brief mechanical restraint (5 min of immobilization) were studied for differences in the growth of their cloacal glands when reared essentially lifelong on short day lengths of 8L:16D. Post-brooding, at 4 wk of age, 96 quail (48 LS + 48 HS) were housed in cages (1 LS and 1 HS male/cage), and the short day light treatment was instigated. Using a digital caliper, cloacal gland (CG) size measurements (length and width, mm) were made biweekly beginning at 42 d of age and ending at 196 d of age (28 wk old). The CG volume (CVOL) was calculated from these measurements using a literature-proposed formula. The CVOL in both lines increased similarly with increasing age from 6 to 12 wk of age. However, beginning at 14 wk of age and thereafter, LS males showed greater (P < 0.05) CVOL than HS ones. No further increases in CVOL were observed in either line at 24 wk of age beyond that seen at 22 wk. This study demonstrated that although both lines show CG development under short days, eventually CG growth becomes comparatively stymied in the HS males. Furthermore, the maintenance of similarly lower CVOL in HS than LS males, CVOL that showed no further increase from 22 to 24 wk of age, suggests that holding these quail lifelong on short days results in, comparatively, yet another permanent negative reproductive consequence in quail selected for exaggerated plasma corticosterone stress responsiveness.